MENYELAMATKAN REMAJA DARI BAHAYA LGBT DENGAN PENDAMPINGAN, PENGENALAN DAN PENDIDIKAN SEKS DI PONDOK PESANTREN SUMATERA BARAT - Mellyarti Syarif; Meri Susanti (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The age of teenagers who are full of jolts is the gateway to early adulthood, this period brings them to drastic changes, physically and psychologically. Psychological changes make adolescents experience the following things